The Relation Between Aggression and Psychotic-Like Experiences in Help-Seeking Adolescents: The Role of Threat/Control-Override Symptoms - Redman, Samantha; Pitts, Steve; DeVylder, Jordan; Link, Bruce G.; Healey, Lindsay V.; Kopelovich, Sarah; Mittal, Vijay A.; Cauffman, Elizabeth; Rouhakhtar, Pamela Rakhshan; Reeves, Gloria M.; Schiffman, Jason (Oxford University Press, 2025)
Psychosis is a heterogeneous phenomenon that emerges across a severity spectrum. Attenuated psychotic symptoms, or psychotic-like experiences (PLEs), reflect potential risk factors for formal psychosis and other clinical outcomes. There has historically been a widespread misconception that individuals who experience symptoms of psychosis are dangerous and prone to aggressive behavior. However, empirical evidence reveals only a modest link between psychosis and aggression. The existing associations are sometimes linked to a set of psychotic symptoms known as threat/control-override (TCO) symptoms that are often amenable to treatment. Despite research linking TCO symptoms and aggressive behavior in formal psychosis samples, studies in populations with PLEs are lacking. In line with the TCO model, we hypothesized that a subset of PLEs representing threat perception and control would have unique positive associations on aggression in the sample. The present study examined the relation between PLEs and aggression in help-seeking adolescents (n = 129). Psychotic-like experiences were assessed by parent/caregiver report (Prime Screen-Revised-Parent/Caregiver Version), and aggression was measured using a parent-rated assessment of adolescent behavior (Behavioral Assessment System for Children, Second Edition).Results supported study hypotheses, revealing small, independent effects of threat perception and control, in addition to a significant combined effect of these variables (TCO) on aggression. Findings support the use of symptom-specific measures of PLEs, including those aligning with the TCO model, to investigate the relation between attenuated psychotic symptomatology and aggression.
Keywords: UMBC EQUIPS Lab